2011
DOI: 10.1246/cl.2011.147
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Resolution of Racemic 1-Heteroarylalkanols by Asymmetric Esterification Using Diphenylacetic Acid with Pivalic Anhydride and a Chiral Acyl-transfer Catalyst

Abstract: A variety of optically active 1-heteroarylalkanols and their esters, which include heteroaromatic moieties, such as 2-furyl, 2-thienyl, 3-thienyl, 2-thiazoyl, 2-benzothiazoyl, and 2-benzoxazoyl groups, are efficiently produced by a novel asymmetric esterification. The transition states that form the desired (R)-esters from the (R)-1-heteroarylalkanols are determined by DFT calculations, and the structural features of these transition states are systematically discussed.Optically active 1-heteroarylalkanols are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(15 citation statements)
references
References 12 publications
(7 reference statements)
1
14
0
Order By: Relevance
“…The results obtained with Cl-PIQ 2 and BTM 3 were rather modest (entries 8 and 9). While we have made no attempt at optimization in these cases, a recent study by Shiina et al 7c has demonstrated that good to excellent enantioselectivities can be obtained in BTM-catalyzed KR of similar substrates using mixed diphenylacetic-pivalic anhydride as the acylating agent.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results obtained with Cl-PIQ 2 and BTM 3 were rather modest (entries 8 and 9). While we have made no attempt at optimization in these cases, a recent study by Shiina et al 7c has demonstrated that good to excellent enantioselectivities can be obtained in BTM-catalyzed KR of similar substrates using mixed diphenylacetic-pivalic anhydride as the acylating agent.…”
Section: Resultsmentioning
confidence: 99%
“…More elaborate acylating agents have not been studied systematically in our group due to their higher cost. However, recent studies by Shiina 7b,c indicate that the use of diphenylacetic-pivalic anhydride often results in dramatically increased selectivity factors. Overall, BTM 3 is the most enantioselective of all ABCs developed to date in the KR of benzylic and propargylic alcohols, as well as several other applications described elsewhere.…”
Section: Resultsmentioning
confidence: 99%
“…The optimal conversion and high selectivity obtained using diphenylacetic anhydride 7 o , and the lack of reactivity using pivalic anhydride 7 c , presented the possibility of using the mixed anhydride 2,2‐diphenylacetic pivalic anhydride 7 r . Mixed anhydrides have been reported to be advantageous in some cases for the KR of point chiral secondary alcohols ,,,,,,,. Generating the mixed anhydride in situ from diphenylacetic acid and pivalic anhydride provided a KR protocol that gave excellent selectivity ( s =50–60) but inconsistent reaction conversion in our hands ( c =8–42 %) .…”
Section: Resultsmentioning
confidence: 85%
“…In a different approach, we recently reported the kinetic resolution of racemic alcohols with achiral carboxylic acids by asymmetric esterification. [3] This reaction proceeded by the formation of a mixed anhydride using carboxylic anhydrides in situ as coupling reagents in the presence of chiral acyltransfer catalysts. As the desired chiral carboxylic esters (R)-iv (R 3 = any alkyl group) were obtained directly in one step from the condensation of alcohols rac-i with free carboxylic acids, it was anticipated that the protocol could be an alternative means by which to achieve asymmetric acylation for the synthesis of natural product derivatives (Scheme 1).…”
mentioning
confidence: 99%